2023
DOI: 10.3126/nmcj.v25i1.53373
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and molecular characterization of methicillin resistant Staphylococcus aureus (MRSA) and vancomycin resistant Staphylococcus aureus (VRSA) in a tertiary care hospital

Abstract: Resistance shown by Staphylococcus aureus to methicillin; mediated by mecA, and vancomycin; mediated by vanA, has led to difficulty in treatment of related infections. Despite reports showing methicillin resistant S. aureus (MRSA) and vancomycin resistant S. aureus (VRSA) in Nepal, and need for their regular surveillance, no study has been conducted on it in our hospital. So, this study is aimed to determine prevalence of MRSA, VRSA and their molecular characterization along with antibiogram. A descriptive cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
0
1
Order By: Relevance
“…17 Our study showed no significant difference in the prevalence of MSRA in males and female. This finding contrast with that of Khanal and Jha, who found the condition to be more prevalent in male than females 18 and also Hasanpour et al, who also found the occurrence of MSRA to be more prevalent in elderly men than women. 19 The S. aureus showed varying susceptibility and resistance to the two antimicrobials (Cefoxitin and Ampicillin) used in the study.…”
Section: Discussioncontrasting
confidence: 88%
“…17 Our study showed no significant difference in the prevalence of MSRA in males and female. This finding contrast with that of Khanal and Jha, who found the condition to be more prevalent in male than females 18 and also Hasanpour et al, who also found the occurrence of MSRA to be more prevalent in elderly men than women. 19 The S. aureus showed varying susceptibility and resistance to the two antimicrobials (Cefoxitin and Ampicillin) used in the study.…”
Section: Discussioncontrasting
confidence: 88%